Aerobic Exercise to Overcome Menstrual Pain in Adolescent Girls at Gemayasih Islamic Boarding School - Nurnisaa AS, Nurnisaa; Hadiaty Y, Siti (International Journal of Health, Medicine, and Sports, 2024)
This study investigated the effectiveness of aerobic exercise in reducing menstrual pain among adolescent girls at Gemayasih Islamic Boarding School. Using a quasi-experimental design with pre-test and post-test measurements, 50 adolescent girls aged 14-17 years were divided into two groups: an intervention group performing aerobic exercise (n=28) and a control group performing jogging (n=22). Pain intensity was measured using the Numeric Rating Scale (0-10) over three menstrual cycles. Results showed that the aerobic exercise group experienced a more significant reduction in pain intensity (from 3.50 ± 0.600 to 1.20 ± 0.300) compared to the jogging group (from 3.60 ± 0.650 to 2.50 ± 0.600). Statistical analysis revealed a significant difference between the groups (p=0.000), with aerobic exercise demonstrating superior effectiveness in pain reduction. The study also found that participants commonly experienced additional symptoms, with emotional instability being the most prevalent (97% in the aerobic group, 90% in the jogging group). These findings suggest that aerobic exercise can serve as an effective non-pharmacological intervention for managing menstrual pain in adolescent girls within boarding school settings.